Canalicular system reorganization during mouse platelet activation as revealed by 3D ultrastructural analysis. (2nd January 2021) - Pokrovskaya, Irina D.; Tobin, Michael; Desai, Rohan; Joshi, Smita; Kamykowski, Jeffrey A.; Zhang, Guofeng; Aronova, Maria A.; Whiteheart, Sidney W.; Leapman, Richard D.; Storrie, Brian
Abstract: The canalicular system (CS) has been defined as: 1) an inward, invaginated membrane connector that supports entry into and exit from the platelet; 2) a static structure stable during platelet isolation; and 3) the major source of plasma membrane (PM) for surface area expansion during activation. Recent analysis from STEM tomography and serial block face electron microscopy has challenged the relative importance of CS as the route for granule secretion. Here, We used 3D ultrastructural imaging to reexamine the CS in mouse platelets by generating high-resolution 3D reconstructions to test assumptions 2 and 3. Qualitative and quantitative analysis of whole platelet reconstructions, obtained from immediately fixed or washed platelets fixed post-washing, indicated that CS, even in the presence of activation inhibitors, reorganized during platelet isolation to generate a more interconnected network. Further, CS redistribution into the PM at different times, post-activation, appeared to account for only about half the PM expansion seen in thrombin-activated platelets, in vitro, suggesting that CS reorganization is not sufficient to serve as a dominant membrane reservoir for activated platelets. In sum, our analysis highlights the need to revisit past assumptions about the platelet CS to better understand how this membrane system contributes to platelet function.